METHODOLOGY FOR EXAMINING THE LINKS BETWEEN TRANSPORT AND THE ECONOMY - Maciej MINDUR (Scientific Journal of Silesian University of Technology. Series Transport)
This paper discusses the findings of studies on the relationship between the world economy and transport, based on the polynomial curve in 1995-2015. The socio-economic measures were reviewed, recognizing that GDP, although not reflecting what is happening in the social sphere, is the best indicator of economic growth, especially its dynamics. The results of the review show a high convergence in the shaping of the polynomial curves representing GDP and total transport, which is confirmed by the closeness of this relationship, as well the relationship between economic development and transport. The coefficients R2 of the variables studied are fully reliable, ranging from 0.9725 to 0.9954.